Equity research Johnson & Johnson- beyond the pharmaceutical industry - Condeço, Marta Soares (2022)
The goal of the Field Lab –Equity Research was to elaborate a report regarding Johnson& Johnson in orderto evaluate the company and arrive at an intrinsic value. There fore, the present document was produced by Diana Patrícia Campos da Silva and Marta Soares Condeço, two students from the master's degree in finance at Nova School of Business and Economics (“Nova SBE”). Before computing the model, an in-depth macro and micro analysis was performed by investigating not only the business segments of the company but also the industry and the overall economy. After that and after considering several assumptions, the outcome was a share price of $225.6thus representing a value higher than the market price. The interpretation is that J&J is trading its stock at a lower price than its fair value. The relative analysis made afterwards reached the same conclusion. Finally, to better understand the price fluctuations when any of the assumptions changed, a sensitivity and scenario analysis was computed. We consider that all the assumptions chosen are fair since they reflect both internal and external features that may affect the company.